1990
DOI: 10.1128/jb.172.6.3534.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the gene encoding cytochrome c550 of Paracoccus denitrificans and analysis of the resultant physiological effects

Abstract: Volume 172, no. 2, p. 990, Fig. 2: The amino acids under nucleotides 388 to 423 were transposed with those under nucleotides 424 to 474; the correct amino acid sequence of cytochrome c550 is shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 0 publications
3
67
0
Order By: Relevance
“…Timkovich and Dickerson [9] determined an X-ray structure at 0.25-nm resolution for cytochrome c550 from strain LMD 22.21, which was based, in part, on an incorrect amino acid sequence and contained only backbone atoms for the C-terminal 13 residues. The sequence was corrected by Ambler et al [10] and confirmed by the sequence of the gene [11]. Benning et al [12] presented a higher resolution X-ray structure based on the correct sequence, but lacking residues 1Ϫ2 and 123Ϫ135, which were missing perhaps as a result of proteolysis during preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Timkovich and Dickerson [9] determined an X-ray structure at 0.25-nm resolution for cytochrome c550 from strain LMD 22.21, which was based, in part, on an incorrect amino acid sequence and contained only backbone atoms for the C-terminal 13 residues. The sequence was corrected by Ambler et al [10] and confirmed by the sequence of the gene [11]. Benning et al [12] presented a higher resolution X-ray structure based on the correct sequence, but lacking residues 1Ϫ2 and 123Ϫ135, which were missing perhaps as a result of proteolysis during preparation.…”
Section: Resultsmentioning
confidence: 99%
“…A 4.6-kb NotI fragment of this plasmid, which contains the mutated cycM gene, was cloned in suicide vector pRVS2, yielding vector pRTd28.22. This plasmid was used in the gene exchange technique described earlier (51) , which all have marked mutations in their chromosomal cycM genes. The correctnesses of the mutations were confirmed by Southern analyses of their chromosomal DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Much of our knowledge on how electrons are transferred from the dehydrogenases to the terminal oxidoreductases stems from the analyses of mutants with mutations in genes encoding electron carriers that make up the respiratory network (9,11,50,51,52,53). However, it has thus far been difficult to understand the exact role of the different types of cytochrome c in situ since mutations in their corresponding genes did not give clear phenotypes if at all.…”
mentioning
confidence: 99%
“…For rapid screening, plasmid DNA was isolated by the alkaline lysis method (15). Chromosomal DNA of P. denitrificans was isolated as described earlier (28). DNA restriction fragments were purified from agarose gels by using GeneClean (Bio 101, Inc., San Diego, Calif.).…”
Section: Methodsmentioning
confidence: 99%